Terror at Bottle Creek - Key, Watt (Farrar Straus Giroux, 2016)
"Thirteen-year-old Cort's father is a local expert on hunting and swamp lore in lower Alabama who has been teaching his son everything he knows. But when a deadly Gulf Coast hurricane makes landfall, Cort must unexpectedly put his all skills--and bravery--to the test"--Provided by publisher.